Espécies reativas de oxigênio e de nitrogênio, antioxidantes e marcadores de dano oxidativo em sangue humano: principais métodos analíticos para sua determinação Reactive oxygen and nitrogen species, antioxidants and markers of oxidative damage in human blood: main analytical methods for their determination - Sandra Mary Lima Vasconcelos; Marília Oliveira Fonseca Goulart; José Benedito de França Moura; Vanusa Manfredini; Mara da Silveira Benfato; Lauro Tatsuo Kubota (Química Nova, 2007)
We review here the chemistry of reactive oxygen and nitrogen species, their biological sources and targets; particularly, biomolecules implicated in the redox balance of the human blood, and appraise the analytical methods available for their detection and quantification. Those biomolecules are represented by the enzymatic antioxidant defense machinery, whereas coadjutant reducing protection is provided by several low molecular weight molecules. Biomolecules can be injured by RONS yielding a large repertoire of oxidized products, some of which can be taken as biomarkers of oxidative damage. Their reliable determination is of utmost interest for their potentiality in diagnosis, prevention and treatment of maladies.